Metoclopramide and acute dystonia: A case report - Thapa, Ashish; Pant, Manish Nath (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Metoclopramide is one of the frequently used antiemetic and prokinetic. The aim of this case report is to emphasize the occurrence of metoclopramide induced acute dystonic reaction. Its prevalence is increasing and can be life threatening. We present a case of 18 years old female, who presented to the emergency of Kathmandu Medical College with the complaints of pain and stiffness of the neck and inability to keep her tongue in her mouth. She developed acute dystonic reactions after her fourth dose of Metoclopramide; which was prescribed for her vomiting associated with dysmenorrhea. The drug was discontinued and 25 mg of intravenous Chlorpheniramine was administered. The symptom subsided in two hours and was discharged with oral Chlorpheniramine. Metoclopramide can cause severe adverse reaction such as acute dystonic reaction, which is of unpredictable nature, physicians should be aware of this bizarre effect and the treatment.